Expanding indication of free hypothenar flap transfer: Sequential pedicled ulnar palm flap transfer to a relatively large hypothenar flap donor site. Issue 1 (January 2022) - Yamamoto, Takumi; Daniel, Bassem W.; Kageyama, Takashi; Sakai, Hayahito; Fuse, Yuma; Tsukuura, Reiko; Yamamoto, Nana
Summary: Background: Free hypothenar flap (HTF) transfer allows sensible soft tissue reconstruction of the fingertip. However, HTF is basically indicated for a relatively small soft tissue defect, as width of an HTF is limited up to approximately 20 mm to allow primary donor site closure. Combined with sequential local flap to an HTF donor site, a larger HTF can be used without the contracture risk. The aim of this study was to evaluate feasibility of free HTF transfer and sequential ulnar palm flap (UPF) transfer (HTF–UPF) for relatively large fingertip reconstructions. Methods: Medical charts of patients who underwent HTF–UPF for fingertip reconstruction were reviewed. An HTF was designed transversely proximal to the proximal palmar crease, and a slightly smaller hemi-spindle-shaped UPF was designed longitudinally on the mid-lateral aspect of the ulnar palm; the UPF was used to close the HTF donor site. Patient and flap characteristics, intra-operative findings, and postoperative results were evaluated. Results: Twelve patients with average age of 42.7 years were included. HTF–UPF procedure was performed on 12 fingers. HTF's length/width ranged from 45/20 to 70/40 mm (average, 52.5/32.1 mm). UPF's length/width ranged from 40/20 to 55/30 mm (average, 46.7/24.2 mm). Time for sequential UPF transfer ranged from 3 to 9 min (average, 5.1 min). All HTFs and UPFs survived without flap necrosis or scar contracture. Postoperative sensation was comparable with the contralateral fingertip. Conclusions: HTF–UPF procedure allows relatively large fingertip reconstruction with a minimum risk of HTF donor site contracture.